Metastatic amelanotic melanoma with cardiac involvement: A case report. Issue 2 (February 2019) - Brusca, Rebeccah M.; Griffin, Jan M.; Miller, Karin; Russell, Stuart D.
Abstract: Metastatic melanoma has a high rate of cardiac involvement and often presents with non-specific symptoms, including heart failure. We report a case of a 41-year-old woman with a remote history of resected flank melanoma, who presented with heart failure progressing to cardiogenic shock and death. Despite extensive workup including chest computed tomography, cardiac magnetic resonance imaging, and endomyocardial biopsy, the etiology of her heart failure was not diagnosed until autopsy revealed metastatic amelanotic melanoma. In patients with unexplained heart failure and a history of melanoma, imaging studies including fluorodeoxyglucose positron emission tomography should be included in the workup to guide early diagnosis and treatment. <Learning objective: This case report highlights the importance of maintaining a high clinical suspicion for malignant melanoma in patients presenting with heart failure of uncertain etiology.>